Prevalence And Social Factors Associated With Postpartum Depression In Urban Areas Of Pakistan: Cross-Sectional Study - Muhammad Moeed Azwar Bhatti; Muhammad Saarim Ashraf; Hafsa Bhatti; Mahwash Jamil; Kaniz Mukhdooma; Zainab Ibrahim (Journal of Rawalpindi Medical College)
Objective: A type of mental sickness known as postpartum depression (PPD), which affects some women after giving birth, is characterized by feelings of melancholy, anxiety, and weariness that can interfere with day-to-day activities and the ability to form attachments with the infant. The social and cognitive development of the infant is said to suffer from PPD. In multiethnic urban areas in Pakistan, this study sought to determine the prevalence and risk factors for postpartum depression.